EFL Teachers’ Voices in Differentiated Instruction - Yuniawati, Deonisia Tyas (EDUPEDIA Publisher, 2024)
All children in Indonesia have an equal right to education at their level, and the curriculum acknowledges the diversity of Indonesian classrooms. Teachers must consequently incorporate this into the design of their lesson plans. In order to give students alternative possibilities for obtaining information, differentiated instruction involves rearranging classroom instruction and learning methodologies. Teachers may be familiar with the idea of varied education, but they frequently struggle to incorporate difference in terms of content, method, and output in their classrooms. In the framework of differentiated education, this thesis investigates the points of view and experiences of EFL (English as a Foreign Language) teachers. The purpose of this study is to hear these teachers' voices as they discuss the opportunities and difficulties that varied education methodologies in various classroom contexts bring. The study highlights the perspectives of EFL teachers on how differentiated instruction should be implemented. The results show how different educational approaches, assessment methods, and classroom management strategies are used by teachers to meet the various learning demands of their students. The study reveals the struggles and obstacles faced by EFL teachers as they attempt to strike a balance between the demands of a standard curriculum and the particular needs of each of their students. It also underlines how important professional development is in giving teachers the abilities and information required for successfully implementing differentiated instruction. The study's conclusion emphasizes the importance of administrative policies, administrative support systems, and teamwork in determining the overall success of courses for differentiated instruction.